An Overview of Antioxidant and Pharmacological Potential of Common Fruits - Hussain, Shabbir; Sajjad, Aqsa; Butt, Shumaila Zulfiqar; Muazzam, Muazzam Ali (Scientific Inquiry and Review, 2021)
This research was conducted to evaluate the antioxidant and pharmacological potential of numerous common fruits. Prunus Domestica (Prunes) are excellent sources of dietary antioxidants and cause the lowering of LDL cholesterol plasma level. Strawberries (Fragaria Ananassa) have ascorbic acid content (5-50 mg/100 g of fresh weight) and are effective in the treatment of oral cancer and cardiovascular diseases. Citrus fruits (Citrus limon) are rich in flavonoids (naringin and hesperidin), polyphenols and vitamin C; the extracts of citrus peels are effective against food borne bacteria. Lime oil from Citrus aurantifolia has been used as a component of skin care products and to impart taste and flavor in the food industry. Grapes (Vitis Vinifera) are rich in phenolic compounds and are active against cancer, cholera, smallpox, nausea, eye infections and skin/kidney/liver diseases. Blackberry (Rubus ulmifolius) contains polyphenol ingredients and has neuroprotection potential against age-related diseases. Different parts of Jamun or Java Plum (Syzygium Cumini) demonstrate an excellent antioxidant and antimicrobial potential and are used as a remedy for diabetes mellitus, leucorrhea, fever, constipation and gastropathy. Ziziphus mauritiana (Jujube) consists of cyclopeptide alkaloid, lupine and ceanathone triterpenes. It can be used in sedatives and analgesic; and exhibits excellent antibacterial and antioxidant potential. Vaccinium oxycoccus (cranberries) have 10mg/100g of ascorbic acid content and its extract can prevent urinary tract infections. Copyright(c) The Authors